Prestige and running events? An investigation on the effect of the former on the latter - Yeo, Matthew Ming Chong (2018)
This study sought to explore how the prestige of a running event affects the intent of half marathon participants to participate in that event. A total of 55 participants were selected through convenience sampling. Participants had to be 18 years old and above and have participated in at least two half marathons, one of which was the Standard Chartered Singapore Marathon (SCSM). Event prestige along with 9 other subscales from the Motivations of Marathoners scale (MOMS) were being incorporated into an online survey. A 2 x 2 mixed ANOVA was conducted to investigate the differences in mean scores in terms of the importance of the prestige of the SCSM between first time (N = 27) and repeated (N = 28) participants and between the importance of the prestige of the SCSM and the prestige of other half marathons (Event A). It was found that there were no significant differences for both comparisons respectively (p = 0.716 > 0.05, p = 0.367 > 0.05). This could possibly be due to reasons such as the less desirable benefits that event prestige brings and the perceived event prestige by participants. It is concluded that event prestige as a motivational factor for participation is an exploratory concept and thus, more research needs to be conducted to acquire a better understanding. Running event organizers can focus more on established aspects such as health orientation and personal goal achievement to attract more participants while maintaining the prestige of the event until a better comprehension is obtained.